PERAN JUMLAH KOMISARIS PADA HUBUNGAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA PERUSAHAAN (STUDI PADA INDUSTRI NON-KEUANGAN DI INDONESIA) - Lorentan, Stephanie Anastasia; Susilawati, Cicilia Erna (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2017)
This study examines the effect of risk profile, earnings, and capital to firm value by using good corporate governance as intervening variable. The sample in this study used banking company listed on the Indonesian Stock Exchange in 2011-2016 with a sample of 40 banking companies. The result of this study showed that direct influence of risk profile and capital to firm value. While earnings variable doesn’t directly affect the firm value. Another result of this study showed good corporate governance intervenes the influence of risk profile and earnings to firm value. While good corporate governance doesn’t interfere with the influence of capital on firm value.